Digitalisasi pembelajaran Bahasa Mandarin dan Budaya Tiongkok - Aprilia, Aisyah Eka; Salsabila, Farah Ummul Atiyatus (Fakultas Sastra Universitas Negeri Malang, 2022)
This article was written with the aim of exploring how to learn Mandarin and Chinese culture through various social media. We examine whether the current digital era can make it easier for beginners to improve their Mandarin language skills. Various advances in information technology have an impact on changes in all aspects of people's lives, including education. This research uses the descriptive qualitative method. Social media such as Youtube, Instagram, Facebook, Blogs, Twitter, and others can be used as a form of embodiment in learning the language and introduction to various Tiongkok cultures. The result of this research found that by using social media, students can get information about Mandarin and Chinese culture quickly. Also, teachers can use various types of material in the form of interesting and interactive content on social media, which consists of Youtube, Instagram, and TikTok.